(NiZ MUZYKALXNO(B- (NPEDOGAGI^ESKOGO NASLEDIQs (NMONOGRAFIQs - (Ns(B,(Nm(B,(NmAJKAPARs ((N~ELQBINSKs (Nmrt OFORMLENIEs, 2017)
(Nw NASTOQ]EM IZDANII PUBLIKU@TSQ LITERATURNO (B-(NTEORETI^ESKIE TRUDA IZWESTNOGO PIANISTA(B,s
Keywords: (NmONOGRAFIQs